الإستقـــالة في التشريــــع الـــوظيفي الجزائـــري - عتوسي, أسماء (جامعة الوادي University of Eloued, 2019)
"ينال موضوع الوظيفة العامة أهمية كبيرة في مجال القانون الإداري، ذلك أن الأمر يتعلق بالنظام العام الذي يطبق على العاملين في مؤسسات الدولة بمختلف أنواعها من أبسط موظف إلى أعلى موظف سام فجميعهم يخضع إلى نفس التشريع. من خلال دراستنا لهذا الموضوع الذي يتضمن إحدى طرق إنهاء العلاقة الوظيفية، وما له من أهمية في الحياة المهنية للموظف والمتمثل في الاستقالة، حيث جاءت هذه الدراسة لتسليط الضوء والوقوف عند أحكامها والإلمام بمختلف جوانبها من خلال تناولها في ظل التشريع الوظيفي الجزائري. توصلنا من خلال هذه الدراسة إلى جملة من التوصيات المرتبطة أساسا بوجود نقص تشريعي وعدم ضبط بعض المسائل لذلك نقترح ما يلي:  النص على الحق في الإستقالة في الباب المخصص للحقوق الخاصة بالموظف لاعتبارها حق أيضا مكفول قانونا.  يفضل ادراج نص صريح يعالج مسألة سكوت الادارة في الرد على طلب الإستقالة بأن تصبح الاستقالة مقبولة بصفة قانونية بدلامن الاستقالة فعلية، وذلك لضمان التكريس القانوني والفعلي للاستقالة  يفضل وضع نص حول جواز سحب طلب الإستقالة قبل البت في هذه الأخيرة من قبل السلطة المختصة بذلك.  النص برفض قبول طلب إستقالة الموظف المحال على التأديب.  ضرورة مرونة الإدارة في الإستجابة لطلب الاستقالة في أجل مناسب لتحقيق التوازن بين مصلحتها ومصلحة الموظف، وتمكينها من سرعة استخلاف الموظف المستقيل في أقرب وقت ممكن وذلك تحقيقا للمصلحتين العامة والخاصة على حد سواء. ""The subject of the public service is of great importance in the field of administrative law. It is a matter of public order, which applies to employees of state institutions of all kinds, from the simplest employee to the highest ranking employee, all subject to the same legislation. Through this study of the subject, which includes one of the ways to terminate the relationship, and the importance of the professional life of the employee, which is the resignation, where the study came to shed light and stand by its provisions and knowledge of various aspects through dealing with them under the Algerian labor legislation. Through this study, we reached a number of recommendations related mainly to the existence of a legislative deficit and lack of control of some of the issues so we suggest the following: The right to resign in the section on employee rights as a right is also guaranteed by law. It is preferable to include an explicit provision dealing with the question of the silence of the administration in responding to the resignation request that the resignation becomes legally acceptable without actually resigning, in order to ensure the legal and effective It is preferable to draft a text on the possibility of withdrawing the request for resignation before deciding on the latter by the competent authority. The text refuses to accept the resignation of the employee assigned to discipline. The need for flexibility of management in responding to the request to resign in a timely manner to achieve balance between its interests and the interest of the employee, and enable them to expedite the use of the resigning employee as soon as possible in order to achieve both public and private interests. "
ماستر اداري
Keywords: الإستقـــالة، القانون، التشريع، القضاء، الوظيفي.; resignation, law, legislation, judiciary, career.